2019
DOI: 10.17707/agricultforest.65.4.06
|View full text |Cite
|
Sign up to set email alerts
|

The Suppression of Potato Pathogens Development During Storage Period as Influenced by Air Medium, Contacting With Natural Potassium Salts

Abstract: One of the urgent problems of agricultural production is preservation of the grown yield, minimizing storage losses, which can reach 30-50 percent. The ways to solve this problem are observed in given article. The analysis of existing methods of products storage based on modern technologies is fulfilled. Using of unique properties of natural potassium salts is admitted to be one of promising technologies for potato and root crops storage. The research program has been launched in Perm Federal Research Center o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The experiments on the effect of the air medium contacting with natural potassium salts on potato storing in special climatic chamber were started in 2017 ( Shalimov, et al, 2019 ) and continued in 2020 in typical storage. In particular, at this stage of research, the use of various methods of saturating the air medium with negative air ions and salt aerosol was studied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments on the effect of the air medium contacting with natural potassium salts on potato storing in special climatic chamber were started in 2017 ( Shalimov, et al, 2019 ) and continued in 2020 in typical storage. In particular, at this stage of research, the use of various methods of saturating the air medium with negative air ions and salt aerosol was studied.…”
Section: Resultsmentioning
confidence: 99%
“…Such environment has the ability to inhibit the growth of potato pathogens (Krasnoshtein et.al., 2008). Preliminary studies fulfilled in Perm Federal Research Center showed that microorganisms colonies number in the air medium saturated with light negative ions and salt aerosol decreased by 13-25% compared with the control ( Shalimov, et al, 2019 ). In this regard, the purpose of this research is to study the impact of these factors on the microclimate of the storage, the ability to inhibit the development of the main pathogens during potato storage, preservation of potato tubers during storage and to test different methods of medium saturation with salt aerosol and light negative ions.…”
Section: Introductionmentioning
confidence: 98%